PENYADARAN HUKUM ORANG TUA SISWA DALAM PENDIDIKAN ANAK USIA DINI (PAUD): Studi Tentang Kesadaran Hukum Orang Tua Siswa Terhadap Program Pembelajaran PAUD - Haniyah Haniyah; M Sifa Fauzi Yulianis; Rachmat Ihya' (Atthiflah: Journal of Early Childhood Islamic Education, 2023)
ABSTRACT Legal awareness is a form of behavior about what should be done based on applicable rules, so far many behaviors of parents of students who lack even show legal awareness of mulai from acts of violence both physical and pskis in early childhood, including support for all rules of child education both inside and outside the classroom . The research method used in this study is a descriptive research method to provide an overview of the problem that is happening, as well as describing what happened at the time of the research, the results of the study showed that the level of legal awareness of parents of early childhood education students, greatly influenced the understanding and mindset of children towards laws or other rules as well as the level of discipline of children at an early age, in the best times of physical and psychic growth and brain development of the child. a form of legal awareness of the parents of students through legal counseling activities for parents of students in an ongoing manner. Dby participating in the Early Childhood Education (PAUD) program together with full parental support for children's learning activities both in the classroom and outside the classroom, as an implementation of legal awareness of parents of early childhood education (PAUD) students in welcoming the future of children to become a generation that has high competitiveness, faith and devotion to God. Keywords : Legal Awareness, Parents, ECCE Students